Hydrotreatment of Cellulose-Derived Bio-Oil Using Copper and/or Zinc Catalysts Supported on Mesoporous Silica-Alumina Synthesized from Lapindo Mud and Catfish Bone - Fahri Swasdika; Wega Trisunaryanti; Iip Izul Falah (Indonesian Journal of Chemistry, 2021)
Catalysts comprising copper and/or zinc supported on mesoporous silica-alumina (MSA) with a high Si/Al ratio were prepared by wet impregnation method. This study investigated the preparation, characterization, and catalytic application of the prepared catalysts for hydrotreatment cellulose-derived bio-oil. The wet impregnation was performed by directly dispersing Cu(NO3)2·3H2O and/or Zn(NO3)2·4H2O aqueous solution into MSA, followed by calcination and reduction under H2 gas stream. The acidity test revealed that metal addition on MSA support increases the acidity of catalysts. During hydrotreatment of cellulose-derived bio-oil CuZn/MSA with total acidity, copper loading, zinc loading, and specific surface area of 24.86 mmol g–1, 5.23 wt.%, 3.15 wt.%, and 170.77 m2 g–1, respectively, exhibited the best performance compared to other prepared catalysts with 90.49 wt.% conversion of liquid product.